Рекуперативний теплообмін на установці газофракціювання та компримування газохімічного виробництва - Маатук, Аббасс (НТУ "ХПІ", 2017)
Дисертація на здобуття наукового ступеня кандидата технічних наук (доктора філософії) за спеціальністю 05.17.08 «Процеси та обладнання хімічної технології» (16 – Хімічна та біоінженерія) – Національний технічний університет «Харківський політехнічний інститут» Міністерства освіти і науки України, Харків, 2017 р. Процеси поділу і зокрема процеси ректифікації газових і рідких сумішей є одними з найбільш енергоємних у промисловості. За оцінками експертів, до 5% всієї енергії, яка використовується людством, споживається саме в цих процесах. Тому дисертація присвячена вирішенню актуальної науково-прикладної задачі підвищення потужності рекуперації теплової енергії в процесах ректифікації широкої фракції легких вуглеводнів (ШФЛВ) і супутніх їм процесах. В результаті аналітичного огляду публікацій виконана класифікація методів збільшення потужності рекуперації теплової енергії в хіміко-технологічних процесах з метою зниження питомого енергоспоживання в промислових процесах. Розглянуто методи внутрішньої теплової інтеграції ректифікаційних колон, як з інтеграцією теплового насоса (ТН) з колоною, так і без інтеграції ТН. Розглянуто роботи, які пов'язані з застосуванням методів Пінч-аналізу для збільшення потужності процесів рекуперації теплоти на установках хімічних виробництв. Зроблено аналіз робіт, які присвячені збільшенню питомої потужності рекуперації теплоти в територіальних виробничих комплексах (Total Site Integration). В аналізі публікацій окремо відзначені роботи піонерів в області Інтеграції Процесів: професора Б. Линнхоффа, професора Р. Сміта, професора Ї. Клемеша, а також роботи вітчизняних вчених: професора Л. Л. Товажнянського, професора П. О. Капустенко, професора Л. М. Ульєва. Аналіз літературних даних дозволив зробити постановку завдань для збільшення питомої потужності процесу рекуперації теплової енергії на установках ректифікації ШФЛВ з отриманням пропан-пентанової, пропан-гексанової, бутанової і ізобутанової фракцій та підібрати методи їх вирішення. Для вирішення даної задачі був обстежений процес рекуперації теплової енергії у цеху газофракціонування нафтопереробного заводу, що складається з двох ліній ректифікації ШФЛВ. Одна з них – отриманням пропан-пентанової, бутанової фракцій, інша – отриманням пентан-гексанової, бутанової і ізобутанової фракцій. Також в територіальний промисловий комплекс входить установка легкого гідрокрекінгу. За допомогою програмного забезпечення UniSim Design побудовані імітаційні моделі процесів поділу ШФЛУ. Аналіз технологічних процесів, їх регламентів, даних імітаційних моделей дозволив записати потокову таблицю процесів, що досліджуються, ця таблиця є цифровим чинником технологічних потоків, що беруть участь в системі теплообміну установки. Також побудована сіткова діаграма існуючої енерготехнологічної системи установки ректифікації ШФЛВ з отриманням пропан-пентанової і бутанової фракцій і визначена потужність процесів рекуперативного теплообміну на установці Qrec = 1230 кВт. Дані, які отримані у результаті, аналізу, дозволили побудувати складові криві процесу ректифікації для існуючої теплообмінної рекуперативної системи і визначити потужність гарячих QHmin =67274 кВт та холодних утиліт QCmin= 65982 кВт, що процес ректифікації споживає в даний час. Аналіз складових кривих дав можливість визначити мінімальну різницю температур між теплоносіями в теплообмінному обладнанні установки ΔТmin = 30 С. Ця величина є параметром, який показує можливість збільшення потужності рекуперації теплової енергії в процесі. На основі теоретичного аналізу системи технологічних потоків процесу ректифікації ШФЛВ, з застосуванням методів пінч-аналізу, визначено оптимальне значення мінімальної різниці температур між теплоносіями ΔТoptmin = 6 °С, і для цього значення побудована сіткова діаграма та технологічна схема проекту реконструкції системи рекуперативного теплообміну і визначено основні параметри нових теплообмінників. В результаті проекту реконструкції, що було запропоновано, потужність рекуперації теплової енергії стане рівною Qrec = 13575 кВт, тобто збільшиться на 1102 %, потужності гарячих і холодних утиліт будуть рівні QHmin = 54914 кВт, QCmin= 53658 кВт, тобто знизяться на 18,37 % і 18,67% відповідно. Теоретичний аналіз системи теплообміну з допомогою апарату складових кривих дозволив визначить обмежувальний фактор для подальшого збільшення потужності рекуперації теплової енергії. Аналіз інтегрованої системи теплообміну процесу ректифікації ШФЛВ з допомогою Великою складовою кривої (ВСК) дозволив усунути обмежувальний фактор з допомогою створення методу оптимальної інтеграції рекомпресійного теплового насосу (ТН) у вже інтегрований процес ректифікації. Побудовані імітаційні UniSim Design моделі інтеграції ТН в обидва процеси ректифікації, які підтвердили збільшення потужності рекуперації теплової енергії в процесі ректифікації ШФЛВ з отриманням пропан-пентанової і бутанової фракції, у порівнянні до існуючого процесу, на 1590 %, а потужність гарячих і холодних утиліт знижується на 72% і 73% відповідно. При інтеграції теплового насоса в процес ректифікації ШФЛВ з отриманням пентан-гексанової, бутанової і ізобутанової фракцій потужність рекуперації збільшиться від значення 1725 кВт до 21270 кВт, тобто на 1233 %, а споживання гарячих утиліт знизиться від значення 41112 кВт до 22490 кВт, тобто на 53%, холодних утиліт знизиться від значення 42812 кВт до значення 23260 кВт, тобто на 54%. Для подальшого збільшення потужності процесів рекуперації теплової ене-ргії виконано аналіз усього територіального комплексу установок ректифікації ШФЛВ (Total Site інтеграція). За допомогою ВСК процесів ректифікації вперше побудовано тепловий профіль комплексу різних установок ректифікації ШФЛВ, аналіз якого дозволив визначити технологічні потоки, на яких можливо встановити додаткові рекуперативні теплообмінні апарати, що дало можливість збільшити потужність рекуперації теплової енергії на 23,4 МВт. В результаті інтеграції комплексу установок загальна потужність рекуперації теплової енергії збільшилася на 1986 %, а потужність гарячих і холодних утиліт зменшилася на 51% порівняно з утилітами процесів у теперішній час. В дисертації для кожного з запропонованих проектів збільшення потужності рекуперації теплової енергії виконано економічний аналіз. В дисертації також вирішена задача збільшення потужності рекуперації теплоти в існуючій двох-потоковій теплообмінній системі з наявністю утилітних шляхів. Визначено залежності температур теплоносіїв і теплових навантажень на теплообмінному обладнанні від додаткової площі поверхні теплообміну і інтенсивності теплопередачі. Визначено найбільш прийнятне розміщення нової поверхні теплообміну і знайдені значення площі поверхні теплообміну для мінімальної приведеної вартості проекту реконструкції та мінімального терміну окупності. Створено метод, алгоритм і програма розрахунку додаткової площі поверхні теплообміну для двохпотокових систем рекуперації теплової енергії.

Thesis for granting the Degree of Candidate of Technical sciences (PhD degree) in specialty 05.17.08 «Processes and equipment of chemical technology» (16 – Chemical and bioengineering) – National Technical University «Kharkiv Polytechnic Institute» of Ministry of Education and Science of Ukraine, Kharkiv, 2017. The processes of separation and especially rectification of gas and liquid mixtures are one of the most energy consuming in the industry. Under the experts estimation, up to 5% of all energy that is used by the humanity is consumed in these processes. That is why the dissertation work is devoted to the solution of ac-tual research-and-applied tasks of increase of capacity of recuperation of heat energy during the processes of rectification of wide fraction of light hydrocarbons (WFLH) and related processes. As a result of the analytical review of the publication, the classification of the methods of increase of capacity of recuperation of heat energy in chemical techno-logical processes with the purpose of decreasing of specific energy consumption intensity in production processes was carried out. The methods of internal heat in-tegration of rectification columns as with integration of the heat pump (HP) from the column and without integration of HP were considered. The works, which were concerned with the application of Pinch Analysis methods to increase the capacity of recuperation of heat energy on the plants of chemical production, were examined. The analysis of works, which were related to the increase of specific energy consumption of heat in the territorial production complexes (Total Site Integration), was carried out. In the analysis of publications, the works of pioneers in the field of Integration Processes such as Professor B. Linnhoff, Professor R. Smith, Professor J. Klemes, and the works of scientists of our country such as Professor L. L. Tovazhnyansky, Professor P. A. Kapustenko, Professor L. M. Uliev, are mentioned in particular. The analysis of published works allowed putting to the tasks of increasing the specific energy consumption of the process of heat recuperation on the rectification plants WFLH with the production of propane-pentanoic, propane-hexane, butane and isobutene fractions and finding the methods of their solution. To solve the given task, the process of heat energy recuperation in the gas-fractionation shop of the oil refinery, which consisted of two lines of rectification WFLH was studied. One of the tasks is to get propane-pentanoic, butane fractions; the other is to get pentane-hexane, butane and isobutene fractions. In addition, the installation of primary creaking enters into the territorial production complex. The simulation models of the separation of WFLH were designed with the help of the software UniSim Design. The analysis of published works allowed putting to the tasks of increasing the specific energy consumption of the process of heat recuperation on the rectification plants WFLH with the production of propane-pentanoic, propane-hexane, butane and isobutene fractions and finding the methods of their solution. To solve the given task, the process of heat energy recuperation in the gas-fractionation shop of the oil refinery, which consisted of two lines of rectification WFLH was studied. One of the tasks is to get propane-pentanoic, butane fractions; the other is to get pentane-hexane, butane and isobutene fractions. In addition, the installation of primary creaking enters into the territorial production complex. The simulation models of the separation of WFLH were designed with the help of the software UniSim Design.The analysis of published works allowed putting to the tasks of increasing the specific energy consumption of the process of heat recuperation on the rectification plants WFLH with the production of propane-pentanoic, propane-hexane, butane and isobutene fractions and finding the methods of their solution. To solve the given task, the process of heat energy recuperation in the gas-fractionation shop of the oil refinery, which consisted of two lines of rectification WFLH was studied. One of the tasks is to get propane-pentanoic, butane fractions; the other is to get pentane-hexane, butane and isobutene fractions. In addition, the installation of primary creaking enters into the territorial production complex. The simulation models of the separation of WFLH were designed with the help of the software UniSim Design. The analysis of published works allowed putting to the tasks of increasing the specific energy consumption of the process of heat recuperation on the rectification plants WFLH with the production of propane-pentanoic, propane-hexane, butane and isobutene fractions and finding the methods of their solution. To solve the given task, the process of heat energy recuperation in the gas-fractionation shop of the oil refinery, which consisted of two lines of rectification WFLH was studied. One of the tasks is to get propane-pentanoic, butane fractions; the other is to get pentane-hexane, butane and isobutene fractions. In addition, the installation of primary creaking enters into the territorial production complex. The simulation models of the separation of WFLH were designed with the help of the software UniSim Design. The analysis of technological processes, their regulations, and data of simula-tion models permitted to record the production line table of the process under the research. Such table is the numeral factor of the technological flows that take part in the system of heat exchange of the plant. And also, the net diagram of the existing capacity technological system of the rectification plant WFLH with obtaining of propane-pentanoic and butane fractions was established. Moreover, the capacity of the processes of the recuperative heat exchange on the plant Qrec=1230 kW was determined. The data, which were obtained as the result of the analysis, allowed to construct composite curves for the rectification process for the existing heat ex-change recuperative system and determined the capacity of hot QHmin =67274 kW and cold utilities QCmin= 65982 kW, which the process of rectification consumed at that moment. The analysis of the composite curves gave the opportunity to deter-mine the minimum temperature difference between the heat transfer agents in the heat exchanging equipment of the plant Тmin = 30 С. This value is the parameter, which shows the ability to increase the capacity of recuperation of the heat energy in the process. On the basis of the theoretical analysis of the system of technological flows of the process of recuperation WFLH, with the use of Pinch Analysis methods, the optimal value of the minimum temperature difference between heat-transfer agents ΔТoptmin = 6 °С was determined, and for this value a net diagram and technological scheme of the project of reconstruction of the system of recuperative heat exchange were constructed. The main parameters of new heat exchangers were defined. As the result of the project of reconstruction, which was proposed, the ca-pacity of the recuperation of heat energy would be Qrec = 13575 kW that is, it would increase by 1102%, the capacity of hot and cold utilities would be QHmin =54914 kW, that is they would decrease by 18.37% and 18.67% accordingly. The theoretical analysis of the heat exchange system with the help of composite curves device allowed establishing limit factor for the further increase of the capacity of heat energy recuperation. The analysis of the integrated heat exchange system of the process of rectifi-cation of WFLH with the help of the big composite curve (BCC) made it possible to eliminate the limit factor with the help of creation of the method of optimum in-tegration of recompression heat pump (HP) into having been integrated process of rectification. The constructed simulation UniSim Design models of HP integration in both processes of rectification, which proved the increase of the capacity of recuperation of the heat energy in the process of rectification WFLH with obtaining of propane-pentanoic and butane fractions comparing to the existing process, by 1590 %, and the capacity of hot and cold utilities decrease by 72 % and 73 % accordingly were created. During the integration of the heat pump in the process of rectification WFLH with obtaining of pentane-hexane, butane and isobutene fractions, the ca-pacity of recuperation increases from the value 1725 kW to 21270 kW that is, by 1233 %, and the consumption of hot utilities will decrease from the value 41112 kW to 22490 kW, that is by 53 %, cold utilities will decrease from the value 42812 kW to the value 23260 kW, that is by 54%. For the further increase of the capacity of the processes of heat, energy recu-peration the analysis of the whole territorial complex of rectification plants WFLH (Total Site Integration) was conducted. Using BCC of rectification processes, for the first time the heat profile of the complex of different rectification plants WFLH was constructed, the analysis of them made it possible to determine technological flows, on which it was possible to install additional recuperative heat exchangers that helped to increase the capacity of recuperation of heat energy by 23,4 MW. In the result of integration of the plants complex the total capacity of the recuperation of the heat energy increased by 1986 %, but the capacity of hot and cold utilities increased by 51 % comparing with the utilities of processes currently. In the dissertation work, the economic analysis for each of the proposed project of the increase of capacity of recuperation of heat energy was carried out. In the dissertation work, the task of increasing the capacity of recuperation of heat in the existing two-flow heat exchange systems in the presence of utility paths was solved. The dependence of heat carries temperature and thermal loading on heat exchange equipment on additional area of heat exchange surface and intensity of heat transfer were determined. The most suitable placement of the new heat exchange surface was determined and the value of the area of the surface of heat ex-change for the minimum present value of the project reconstruction and minimum payback term were found. The method, algorithm and program of the calculation of the additional area of the surface of the heat exchange for two-flow systems of the recuperation of heat energy were created.
Regenerative heat exchange in the fractionation and compression of the gas of chemical production
Keywords: дисертація; енергія теплова; ректифікація; фракція; вуглеводні легкі; інтеграція; насос тепловий; модель імітаційна; теплообмін; апарат теплообмінний; мережа теплообмінна; пінч аналіз; recuperation; thermal energy; rectification; wide fraction; light hydrocarbons; process integration; heat pump; simulation model; heat transfer; heat exchanger network; heat exchanger; pinch analysis; UniSim Design; Total Site; 66.045.1; 662.99